RELEASE MAYOR'S PROPOSED TAX INCREASE WOULD HURT NEW YORK CITY BUSINESSES - MCCORMICK,BJ (Tufts Archival Research Center, 2007)
Press release regarding Mayor Bloomberg's proposal to raise cigarette taxes in New York City. Claims that the raise in the tax will hurt small businesses and lower revenues as people will buy their cigarettes elsewhere. States that Philip Morris supports the initiative to reduce youth smoking, but believes that there are better more effective ways to do it.